The Value of Santri in Political Moments: an Identity - Min Hajul Abidin; Yang Dong (The Institute of Research and Service Community IPMAFA Pati, 2020)
Nahdlatul Ulama (NU) is one of the largest religious organizations in Indonesia. The santri community that is very identical to NU has contributed to Indonesia's development. When viewed from history, Santri were actively involved in Indonesian politics. The contribution of the santri is seen in various strategic positions of the country. The purpose of this study was to determine the attitude of the santri identity in political moments. This study uses a case study method to determine the process and central dynamics of santri in political activity. Semi-structured interviews were used to determine the identity construction of two subjects who had different backgrounds, but both were NU members who were raised in the santri tradition. The results showed that the santri's attitude did not have a particular patron/command and was amoeba/spread in various positions. Santri builds a unique identity as pride and has more value than other groups. Another result shows that political activity is considered an activity in worship.